Pentahelix Policy Management Paradigm as A Model for Disaster Management in Bojonegoro Regency East Java - Agung Subagyo; Rudy Handoko; Hary Wahyudi (LPPM of NAROTAMA UNIVERSITY, 2022)
Purpose: The purpose of this research is to describe the implementation of the pentahelix of disaster management and the paradigm shift to find obstacles and develop an ideal and practical disaster management model. Design/methodology/approach: This study uses a descriptive type of research with a qualitative approach. Data collection techniques using in-depth interviews. The data analysis technique uses data reduction, data presentation, and drawing conclusions. The data validity technique uses source triangulation and data triangulation. Findings: The results showed that the pentahelix management as a disaster management policy in Bojonegoro Regency was not optimal. Research limitations/implications: The theoretical implication is that the collaboration model that reflects pentahelic management has not been optimally formed, the role of each element of non-governmental organizations is not optimal. Practical implications: The practical implication is the application of disaster pentahelix management in Bojonegoro Regency. Originality/value: The originality of this research is an added value for researchers. Paper type: a Research paper